Solving an one-dimensional cutting stock problem by simulated annealing and tabu search - Meghdad HMA Jahromi; Reza Tavakkoli-Moghaddam; Ahmad Makui; Abbas Shamsi (Journal of Industrial Engineering International, 2012)
A cutting stock problem is one of the main and classical problems in operations research that is modeled as LP problem. Because of its NP-hard nature, finding an optimal solution in reasonable time is extremely difficult and at least non-economical. In this paper, two meta-heuristic algorithms, namely simulated annealing (SA) and tabu search (TS), are proposed and developed for this type of the complex and large-sized problem. To evaluate the efficiency of these proposed approaches, several problems are solved using SA and TS, and then the related results are compared. The results show that the proposed SA gives good results in terms of objective function values rather than TS.
Keywords: 650; one-dimensional cutting stock problem; mathematical model; simulated annealing; tabu search